2015
DOI: 10.4293/jsls.2015.00046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Primary Care Physicians' Referral for Bariatric Surgery

Abstract: Background and Objectives:Bariatric surgery has been shown to be an effective weight loss treatment for the morbidly obese, but some primary care physicians remain hesitant about postoperative treatment and management of patients who have undergone the surgery and recommend it to their obese patients infrequently. The purpose of this study was to evaluate perceptions of primary care physicians of the role of bariatric surgery in the management of obese patients and to identify possible barriers to treatment.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 14 publications
3
49
0
Order By: Relevance
“…In our study 75.5% of physicians were able to explain to their patients how the bariatric operations are performed, and 69.8% of respondents could name the most commonly performed bariatric procedures. Tork et al published in 2015 results of a survey presented to primary care physicians which indicated that all respondents were aware of the benefits of bariatric surgery, including diminishing diabetes, hypertension and hyperlipidemia [21]. A publication by Auspitz et al showed that 48.1% of physicians responding to the survey support metabolic surgery for patients with diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study 75.5% of physicians were able to explain to their patients how the bariatric operations are performed, and 69.8% of respondents could name the most commonly performed bariatric procedures. Tork et al published in 2015 results of a survey presented to primary care physicians which indicated that all respondents were aware of the benefits of bariatric surgery, including diminishing diabetes, hypertension and hyperlipidemia [21]. A publication by Auspitz et al showed that 48.1% of physicians responding to the survey support metabolic surgery for patients with diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Also most of the physicians (93.6%) agree that metabolic surgery can help to reduce treatment costs for syndrome X. The survey by Tork et al showed that most respondents (59%) reported that at least 1 in 4 of their patients had a BMI ≥ 35 kg/m 2 , but only 9% indicated that they frequently or almost always refer their morbidly obese patients to bariatric surgeons [21]. In a study by Auspitz et al , 87% of physicians had referred patients for bariatric surgery, but most (70.2%) had referred no more than 5% of their morbidly obese patients within the previous 12 months [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to get listed for surgery, patients often need PCP referral. Tork et al evaluated potential barriers to BS referral among PCPs in Ohio [43].…”
Section: Implementation Of Bariatric Surgery Into the Health-care Systemmentioning
confidence: 99%